Efficacy of Nanosil and Listerine Antiseptics for Infection Control in Dental Unit Waterline - Omidpanah, Neda; Najafi, Farideh; Abiri, Ramin (Journal of Dental School, 2020)
Objectives The aim of this study was to compare the antibacterial efficacy of two antiseptic agents namely Nanosil and Listerine for controlling water contamination. Methods A In this experimental study, six dental units were divided into three groups of A, B, and C. First, sampling of the water from the turbines’ water ducts and the dental air-water sprays was performed early in the morning during two consecutive weeks on Saturdays (the first working day) and Wednesdays (the last working day). The samples were sent to a laboratory in sterile containers for bacterial colony counting. Next, group A and B units underwent decontamination once a week by Nanosil (1% hydrogen peroxide + silver ion) and Listerine, respectively. Group C was the control group. Afterwards, sampling was conducted again as in stage 1 to determine the bacterial colony count. Results The Wilcoxon test indicated a statistically significant difference in the mean bacterial count between the samples taken before and after decontamination in Nanosil and Listerine groups, and the mean bacterial count was lower in the Nanosil group than in the Listerine group (P<0.001). A statistically significant difference was also found in the mean bacterial count between samples taken on Saturdays and Wednesdays before decontamination, and the mean bacterial count was higher on Saturdays than on Wednesdays (P<0.001). Conclusion Both Listerine and Nanosil were effective in decreasing the microbial colony count in the dental unit water lines (DUWLs). The mean bacterial count was lower in the Nanosil group than in the Listerine group.